APPROPRIATE FORAGE MANAGEMENT IN COCONUT PLANTATION CROPS - Kaligis, David A.; Anis, Selvie D. (Proceeding Buffalo International Conference, 2013)
Utilization of forages grown underneath the plantation crops is widely practices in the region of Southeast Asia and in the Pacific island. Since the plantation crops do not fully utilize all incoming radiation and nutrients, their competition with natural vegetation for nutrients is inevitable. In coconut plantation native forages and natural vegetation cannot survive under heavy grazing due to lack of grazing management practiced by farmers. This will lead to overgrazing and compacting the soil and in some circumstances triggering erosion, changing in botanical composition due to invasive weeds, and disappearance of the planting forages species. This disappearance is also probably due to other factors such as intolerance of those species in the shaded environment. However, this is not the case. Although shade tolerance species are planted, the pasture run-down still occurs. To overcome this problem there are three new approaches. The first one is that defoliation should based on biogeochemical process consideration. Â It is should pay attention on the rhizosphere environment to ensure the nutrients uptake by forage, especially grasses is fulfilled.Â The second one is that defoliation should ensure the health of the grass subject to cutting. With the climate change phenomenon, where the air CO2 is abundance, following by the increasing of air temperature, the time of defoliation or grazing should be focused on counting the accumulation of heat unit rather than focusing on forageâs age. The third one is that the appropriate grazing systems and stocking rate should take into account, to ensure the plant to have ability to recover after grazing.Â Â